High genetic risk for depression as an independent risk factor for mortality in patients referred for coronary angiography - Krämer, Robert; Moissl-Blanke, Angela P.; Lorkowski, Stefan; Krämer, Bernhard; Lehtimäki, Terho; Mishra, Binisha H.; Mishra, Pashupati P.; Leipe, Jan; März, Winfried; Kleber, Marcus E.; Müller-Myhsok, Bertram; Delgado Gonzales de Kleber, Graciela (Frontiers in Cardiovascular Medicine, 2023)
BackgroundDifferent observations have suggested that patients with depression have a higher risk for a number of comorbidities and mortality. The underlying causes have not been fully understood yet.AimsThe aim of our study was to investigate the association of a genetic depression risk score (GDRS) with mortality [all-cause and cardiovascular (CV)] and markers of depression (including intake of antidepressants and a history of depression) in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study involving 3,316 patients who had been referred for coronary angiography.Methods and resultsThe GDRS was calculated in 3,061 LURIC participants according to a previously published method and was found to be associated with all-cause (p = 0.016) and CV mortality (p = 0.0023). In Cox regression models adjusted for age, sex, body mass index, LDL-cholesterol, HDL-cholesterol, triglycerides, hypertension, smoking, and diabetes mellitus, the GDRS remained significantly associated with all-cause [1.18 (1.04-1.34, p = 0.013)] and CV [1.31 (1.11-1.55, p = 0.001)] mortality. The GDRS was not associated with the intake of antidepressants or a history of depression. However, this cohort of CV patients had not specifically been assessed for depression, leading to marked underreporting. We were unable to identify any specific biomarkers correlated with the GDRS in LURIC participants.ConclusionA genetic predisposition for depression estimated by a GDRS was independently associated with all-cause and CV mortality in our cohort of patients who had been referred for coronary angiography. No biomarker correlating with the GDRS could be identified.
Veröffentlicht: 26. Juni 2023
Gesehen am 04.08.2023